On Abnormally Factorizable Finite Solvable Groups - Vasil'ev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study hereditary formations closed with respect to the operation of taking products of abnormal subgroups of finite solvable groups. We obtain a constructive description of solvable local hereditary formations of finite groups with the property indicated.